COVID-19 outbreak investigation in a quarantine facility: is SARS-COV-2 exhibiting lesser known routes of spread? - Pathak, Sukant M.; Patra, Vinod K.; Abraham, Dennis; Mishra, Arpit; Khandelwal, Nitish; Krishnan, Anup (International Journal Of Community Medicine And Public Health, 2021)
Background: An institutional quarantine facility in India reported 5 cases in 9 days. The latter 2 cases incited a suspicion of internal outbreak as they were residing in a different room than the index cases and onset of symptoms was after the expiry of quarantine period. Subsequently, 75 more cases tested positive from this facility. Methods: A retrospective-prospective study was conducted. Data regarding the travel history, health-events thereafter, daily activities, layout of the facility and standard procedures followed in the facility was collected. The epidemiological pattern of presentation and evolution of cases was studied. Results: The outbreak pattern and investigation revealed a common bathroom as the cause of intra-floor spread. Inter-floor spread was also observed and 93.75% cases were detected from rooms using their floor bathrooms located vertically below one another and interconnected by plumbing systems. SAR for room contacts of index cases was 90% and SAR was 82.14% for bathroom contacts of index cases. The positivity rate amongst individuals assigned bathroom number 1 on the floors vertically located below the top floor was 64.10%. Conclusions: The investigation and results show local spread of SARS-CoV-2 through usage of common bathroom facility. An interesting trend of inter-floor spread with concentration of cases only in the rooms dedicated to vertically located bathrooms was found which indicates spread through waste-water plumbing system, a phenomenon previously observed in SARS-CoV in 2003. Single floor quarantine facilities are recommended with lesser dependency on common bathrooms.